Multiphase Flow in Pipeline - Khairul Syazwan Abu Samah, Khairul Syazwan (Universiti Teknologi Petronas, 2009)
Transferring oil and gas using pipeline is common way of how the oil and gas industry operate their business. Pipeline is a very economical way to transport large quantities of oil and gas over land. The Transferring of fluids in pipes needs a lot of calculation and consideration. Multiphase flow occurs in transferring oil using pipeline as multiple component are present such as oil and water during the transfer to the refinery plant. In this project, we would like to determine the pressure drop in the pipe as per length of the pipe. The theory of the project lies in the concept of fluid mechanics where the study of fluid and force on them